Folding by Skinning - Ma, Chunyang; Zhu, Lifeng (Computer animation and virtual worlds, 2025)
ABSTRACT We propose a novel method, entitled “Folding by Skinning”, which creatively integrates skinning techniques with folding simulations. This method allows users to specify a two‐dimensional crease pattern along with the desired folding angles for each crease. Based on this input, the system computes the final three‐dimensional shape of the fold. Rather than employing costly physics‐based simulations, we explore the skinning method, noted for its effectiveness in handling the geometry of the folded shape. We recommend extracting the skinning weights directly from the user‐defined crease patterns. By combining the obtained skinning weights with the user‐input folding angles, the initial shape undergoes dual quaternion skinning to produce the folding result. Users can further optimize the shape using post‐processing and targeted filtering of weights to generate more realistic results. Our experimental results demonstrate that “Folding by Skinning” yields high‐quality outcomes and offers relatively fast computation, making it an effective tool for computer‐aided design, animation, and fabrication applications. Illustration of the proposed “Folding by Skinning” method, where a 2D crease pattern is folded into a 3D shape by applying skeleton‐based transformations with specified angles. The figure shows the initial skeleton setup, and presents the resulting folded shape.